Career adaptability, occupational identity, and psychologica well-being after a career change during the covid-19 pandemic - Kutu, Siyamthanda (University of the Witwatersrand, Johannesburg, 2024)
OBJECTIVE: This study aims to explore the relationship between career adaptability, occupational identity, and Psychological Well-being at Work in South African employees who experienced career change during the COVID-19 pandemic. The study is framed within the Career Construction Theory where the pandemic is contextualised as a career shock. METHODS: Employing a quantitative approach, this study adopts a correlational, non-experimental, cross-sectional research design. Purposive sampling, including criterion-based and snowball sampling techniques, was utilized to recruit participants. The sample comprised 62 South African employees who experienced career changes between 2020 and 2022 due to the pandemic's impact on the labour market. Data w as collected through structured online questionnaires, incorporating validated scales. Ethical considerations were addressed, ensuring informed consent, confidentiality, and minimal harm to participants. RESULTS: Regression analysis revealed significant positive relationships between career adaptability, occupational identity, and Psychological Well-being at Work. Specifically, both career adaptability and occupational identity emerged as strong predictors of Psychological Well-being at Work among the participants. Descriptive statistics provided insights into the sample characteristics, indicating a diverse range of career change experiences during the pandemic. The study under scores the importance of fostering adaptability and building a robust occupational identity to enhance employees' psychological well-being amidst career transitions, particularly in times of crisis like COVID-19.
A research report Submitted in fulfillment of the requirements for a Master of Arts , In the Faculty of Humanities , School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; psychological well-being at work; occupational identity; career adaptability. COVID-19; career change; SDG-3: Good health and well-being; SDG-4: Quality education